Improved design of passive wireless sensor for ultra-high temperature environment and its back-end circuit measurement system - Li, Deming (Frontiers in Mechanical Engineering, 2025)
IntroductionAn improved passive wireless sensor is presented for ultra-high temperature environments, utilizing a folded Complementary Split-Ring Resonator (CSRR) structure. A dedicated back-end circuit measurement system is also developed to support the improved sensor.MethodsThe sensor design was optimized with an aluminum nitride ceramic substrate and a platinum layer, incorporating distributed compensation to enhance thermal stability. A matching back-end circuit measurement system was designed for high-sensitivity signal reception and processing.ResultsPerformance testing showed that at 1,000 °C, the quality factor was increased from 241 to 418, and the sensitivity was raised from 10.89 to 17.12. The temperature coefficient of frequency was significantly improved from –14.23 ppm/°C to –3.76 ppm/°C, demonstrating superior stability. Measurements showed that the back-end system achieved a mere 0.02 GHz error in resonant frequency compared to a network analyzer, with a total test error below 1%.DiscussionThe proposed sensor effectively minimizes performance degradation at high temperatures, achieving high-accuracy and stable wireless signal detection. This work provides a reliable passive sensing solution for real-time monitoring in ultra-high temperature conditions.